2004
DOI: 10.1111/j.1349-7006.2004.tb03199.x
|View full text |Cite
|
Sign up to set email alerts
|

DE‐310, a novel macromolecular carrier system for the camptothecin analog DX‐8951f: Potent antitumor activities in various murine tumor models

Abstract: he effect of current therapeutic agents appears when the agent acts on the target organ in the body. Since drug molecules that are distributed to organs that are not targeted may cause side effects, treatment is generally performed using a dose at which efficacy is obtained without unacceptable side effects. However, most antitumor chemotherapeutic agents show clinical effects only at doses that cause side effects such as digestive toxicity and myelosuppression. Therefore, in the development of new antitumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…20,21) Our previous studies have shown that DE-310 elicits significant anti-tumor activity in various tumor models, whereas the activity occurred at lower doses and with a more profound effect than DX-8951 alone. 8) High levels and prolonged retention of conjugated DX-8951, DX-8951, and G-DX-8951 have been observed in tumor tissues after intravenous injection of DE-310 in Meth A tumor-bearing mice. 26) Thus, liberated DX-8951s are believed to exhibit a cytotoxic effect in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21) Our previous studies have shown that DE-310 elicits significant anti-tumor activity in various tumor models, whereas the activity occurred at lower doses and with a more profound effect than DX-8951 alone. 8) High levels and prolonged retention of conjugated DX-8951, DX-8951, and G-DX-8951 have been observed in tumor tissues after intravenous injection of DE-310 in Meth A tumor-bearing mice. 26) Thus, liberated DX-8951s are believed to exhibit a cytotoxic effect in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…7) It has been demonstrated that a single dose of 11.4 mg/kg DE-310 exhibited stronger anti-tumor activity in mice than repeated doses (10 mg/kg daily for 5 d) of DX-8951f (exatecan; DX-8951 monomethansulfonate salt). 8) Taking into account that DX-8951f belongs to time-dependent anti-cancer drugs, 9) slow release of DX-8951 from DE-310 in addition to long-term retention in tumor tissues would have been beneficial in exhibiting such an effective anti-tumor activity.…”
mentioning
confidence: 99%
“…The degree of tissue perfusion may also have some bearing on the relatively high concentrations of all three drug components observed in the spleen and peritoneum of patient 3. The high levels of drug determined in bile and to a lesser degree the gall bladder is supportive of the preclinical pharmacokinetic data that determined that the primary route of excretion of DX-8951 and its metabolites was the feces [44].…”
Section: Discussionmentioning
confidence: 88%
“…Pre-clinical studies have shown that DE-310 elicits anti-tumor activity in various tumor models, whereas the activity occurred at lower doses and with a more profound effect than with DX-8951 alone [40]. Furthermore, high levels and prolonged retention of conjugated DX-8951 and free DX-8951 have been observed in tumor tissues after the dose of DE-310 in Meth A (fibrosarcoma) mice [41].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation